Implementasi Model Pembelajaran PBL (Problem Based Learning) Berbasis Fenomenologi Pada Pembelajaran IPAS Untuk Meningkatkan Berpikir Kritis Siswa Madrasah Ibtidaiyah - Asmaul Fauziyah; Nurul Agustin; Ria Resti Fauziah; Rahmat Rudianto; Ainul Fithriyah; Muhammad Luthfi Efendi (InsightEd, 2026)
The main problem in science and social studies (IPAS) learning at elementary schools is the low level of student engagement and the lack of critical thinking skills due to the dominance of conventional teaching methods. This study aims to improve students’ learning activities and outcomes through the implementation of the Problem Based Learning (PBL) model. The research method used was Classroom Action Research (CAR) with the Kemmis & McTaggart model, carried out in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 37 fourth-grade students of MI Miftahul Huda Gempol Kurung Menganti Gresik in the 2025/2026 academic year. Data were collected through observation, tests (pretest and posttest), and documentation, and analyzed both qualitatively and quantitatively. The results showed an improvement in teacher activity from 77.63% to 90.78%, and student activity from 75.52% to 88.15%. The average pretest score increased from 62.8% to 75.4%, while the posttest score rose from 71.3% to 82.2%. The percentage of students achieving mastery also improved significantly from 43.2% in cycle I to 83.7% in cycle II. Thus, the implementation of PBL proved effective in enhancing students’ learning activity, engagement, and critical thinking skills in IPAS learning at the elementary school level.